Cannabinoid-hypocretin cross-talk in the central nervous system: what we know so far - Flores, África; Maldonado, Rafael; Berrendero, Fernando (Frontiers in Neuroscience, 2013)
Emerging findings suggest the existence of a cross-talk between hypocretinergic and endocannabinoid systems. Although few studies have examined this relationship, the apparent overlap observed in the neuroanatomical distribution of both systems as well as their putative functions strongly point to the existence of such cross-modulation. In agreement, biochemical and functional studies have revealed the existence of heterodimers between CB1 cannabinoid receptor and hypocretin receptor-1, which modulates the cellular localization and downstream signalling of both receptors. Moreover, the activation of hypocretin receptor-1 stimulates the synthesis of 2-arachidonoyl glycerol culminating in the retrograde inhibition of neighbouring cells and suggesting that endocannabinoids could contribute to some hypocretin effects. Pharmacological data indicate that endocannabinoids and hypocretins might have common physiological functions in the regulation of appetite, reward and analgesia. In contrast, these neuromodulatory systems seem to play antagonistic roles in the regulation of sleep/wake cycle and anxiety-like responses. The present review attempts to piece together what is known about this interesting interaction and describe its potential therapeutic implications.